Kepatuhan Diet dan Olahraga Pada Penderita Diabetes Mellitus Tipe 2 : Studi Kasus Kontrol di Puskesmas Tlogosari Wetan - Janardani, Andini Talitha; Widjanarko, Bagoes; Sutiningsih, Dwi; Muh, Fauzi; Suwandi, Amad (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Indonesia faces a triple burden of disease, with rising non-communicable diseases (NCDs) like diabetes mellitus (DM) increasing health costs and mortality. DM ranks among the top causes of death, especially in Central Java and Semarang. DM a chronic metabolic condition, is on the rise worldwide, including in Indonesia. This research examines dietary adherence in productive-age type 2 DM patients at Tlogosari Wetan Public Health Center, Semarang..Methods: Case-control quantitative analytic observational research was used. The target population was 44,154 productive-age type 2 diabetes mellitus patients in Tlogosari Wetan Public Health Center's operating region in 2023. Total 21 respondents, 108 diabetic diet adherent and 108 non-adherent patients were involved in this study. Univariate, bivariate, and multivariate analysis were used.Result: Based on multivariate analysis, it was found the knowledge (OR 4.05 p-value 0.000), self-motivation (OR 2.49 p-value 0.007), perception (OR 5.48 p-value 0.000), participation in nutrion counseling (OR 2.45 p-value 0.013), and the role of health workers (OR 2.37 p-value 0.012) are significant risk factors influencing dietary adherence among productive-age individuals with diabetes mellitus at Tlogosari Wetan Public Health CenterConclusion : Non-adherence among patients with diabetes mellitus is influenced by various factors including lack of knowledge, low motivation, economic constraints, and limited family support. Improving patient education, increasing healthcare support, and engaging families are important strategies to improve adherence and health outcomesKeywords : diabetes mellitus; diet; compliance, exercise